2019
DOI: 10.1001/jamanetworkopen.2019.5776
|View full text |Cite
|
Sign up to set email alerts
|

Association of Midlife Cardiovascular Risk Profiles With Cerebral Perfusion at Older Ages

Abstract: Key Points Question Is midlife cardiovascular risk associated with cerebral blood flow in older age, and does this association vary with age? Findings In this longitudinal cohort study of 116 older adults without dementia, higher cardiovascular risk scores during a 20-year period were significantly associated with lower cerebral blood flow to the medial temporal, parietal, and occipital cortices. The association varied during the life span such that cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 63 publications
6
29
1
Order By: Relevance
“…This did not remove all the effects of FSRS, so FSRS makes a unique contribution to lower GM density, presumably based on vascular pathology beyond a simple function of time ( Uiterwijk et al , 2018 ). In a recent study of a subset ( N = 116) of the Whitehall II imaging sub-study, we found that cardiovascular risk in midlife was significantly associated with lower GM perfusion at older ages, whereas this association was not significant for cardiovascular risk in later life, which lends further support to these results ( Suri et al , 2019 ). FSRS is a composite score and is incremental with age, which makes it difficult to estimate when it starts to affect GM, and when its effects become evident.…”
Section: Discussionsupporting
confidence: 65%
“…This did not remove all the effects of FSRS, so FSRS makes a unique contribution to lower GM density, presumably based on vascular pathology beyond a simple function of time ( Uiterwijk et al , 2018 ). In a recent study of a subset ( N = 116) of the Whitehall II imaging sub-study, we found that cardiovascular risk in midlife was significantly associated with lower GM perfusion at older ages, whereas this association was not significant for cardiovascular risk in later life, which lends further support to these results ( Suri et al , 2019 ). FSRS is a composite score and is incremental with age, which makes it difficult to estimate when it starts to affect GM, and when its effects become evident.…”
Section: Discussionsupporting
confidence: 65%
“…The relationship between late-life BP and cognition may be determine by the presence and chronicity of past hypertension. In very recently published data from the ARIC study, a prospective cohort study that included 4,761 participants with 24-year followup and BP measurements at midlife and at late life, those with midlife and late-life hypertension (hazard ratio, 1.49) and those with midlife hypertension and late-life hypotension (hazard ratio, 1.62) had higher risk for incident dementia compared with those who remained normotensive (35).…”
Section: Hypotension and Risk Of Cognitive Impairment/dementiamentioning
confidence: 99%
“…In summary, imaging studies in AD have shown that dysregulation for CBF and rCBV are critically involved in the pathogenesis of the disease. Changes in rCBF occur earlier than rCBV during the disease course [98], where metabolic and vascular risk factors have been implicated as a driver of hemodynamic disturbances [102,103]. Consistent, experimental studies have shown that these risk factors compromises cerebral perfusion, contribute to cognitive impairment and enhances AD pathology [104,105].…”
Section: Dysregulation Regional Rcbf and Volumementioning
confidence: 99%